'People miss people': A study of school leadership and management in the four nations of the United Kingdom in the early stage of the COVID-19 pandemic. (May 2021) - Beauchamp, Gary; Hulme, Moira; Clarke, Linda; Hamilton, Lorna; Harvey, Janet A
The COVID-19 pandemic has confronted school leaders across the four devolved nations of the United Kingdom (UK) with a period of exceptional crisis. This responsive, small-scale, but UK-wide study focuses on headteacher perspectives on leadership and management in the initial stages of this pandemic, contributing to our understanding of this crucial period. The headteacher respondents met the multiple predicaments and situational ambiguities of the pandemic with a resilience which drew heavily upon the strengths of pre-existing structures and teams. They were required to provide effective emotional and moral leadership in uncharted and rapidly shifting territory. They spoke most eloquently of how they developed pragmatic, versatile and personally reassuring approaches to communication with parents, staff, pupils, and a range of external agencies, all of which were also facing extraordinary circumstances with varying degrees of resilience. The paper concludes by conceptualising the key elements of headteachers' leadership and management, both inside and outside of school, at in the early stages of societal crisis.